Antagonistic interaction between TTA-A2 and paclitaxel for anti-cancer effects by complex formation with T-type calcium channel. Issue 6 (13th April 2022) - Kumari, Neema; Dalal, Vikram; Kumar, Pravindra; Rath, Subha Narayan
Abstract: Studies have shown that in cancer cells, there is an increased T-type calcium channel (TTCC) expression compared to healthy cells. Therefore, the studies targeting TTCC for cancer therapy have shown many positive outcomes. Here, we have used TTA-A2- a potent TTCC inhibitor as a test drug, and paclitaxel (PTX)- a tubule-binding anti-cancer agent as a positive control. Blocking TTCC has shown to overcome resistance in cancer cells towards anti-cancer drugs by reducing calcium influx, and some studies have shown that PTX treatment also reduces the intracellular calcium signaling in cells. So, there is a possibility that PTX might be interacting with calcium channels. Since, drug-drug interaction can cause severe side-effects, or alter the actions of each other; we aim to study the interactions among TTA-A2, PTX, and TTCC. In this study, we have used computational analysis to test the binding of TTA-A2 and PTX with TTCC. To confirm the in-silico result, we further tested these drugs in a 3D spheroid model of A549, a lung adenocarcinoma cell line. The in-silico result showed that both the drugs, TTA-A2 and PTX, could interact at the same site of TTCC to form a higher stable complex as compared to the TTCC-native. The in vitro result showed the antagonistic interaction between the drugs when they are used at the same time. By using the sequential treatment, the spheroids were sensitized by TTA-A2, before treating with PTX. The result indicated that sequential treatment could help to overcome the antagonistic interaction between the two drugs. Communicated by Ramaswamy H. Sarma